Brief Report: Arthritis in KRN T Cell Receptor–Transgenic Mice Does Not Require Interleukin‐17 or Th17 Cells. Issue 8 (27th July 2016) - Auger, Jennifer L.; Cowan, Hannah M.; Engelson, Brianna J.; Kashem, Sakeen W.; Prinz, Immo; Binstadt, Bryce A.
Abstract : Objective: Th17 cells and interleukin‐17 (IL‐17) cytokine family members are implicated in the pathogenesis of many rheumatic diseases. Most studies in mouse models of inflammatory arthritis have demonstrated a key role for the proinflammatory cytokine IL‐17A and its receptor, the IL‐17 receptor (IL‐17R) A/C heterodimer. The aim of this study was to use a rigorous genetic approach to evaluate the contribution of Th17 cells and IL‐17 in the autoantibody‐dependent KRN T cell receptor–transgenic mouse model of arthritis. Methods: We bred KRN mice expressing the major histocompatibility complex class II molecule A g7 (referred to as K/B/g7 mice) and genetically lacking the related cytokines IL‐17A and IL‐17F or their critical receptor subunit, IL‐17RA. Using bone marrow transplantation, we generated mice in which hematopoietic cells from K/B/g7 donor mice lacked the key Th17‐differentiating transcription factor, retinoic acid receptor–related orphan nuclear receptor γt (Rorγt). Results: K/B/g7 mice lacking both IL‐17A and IL‐17F produced normal titers of pathogenic autoantibodies, and arthritis developed in a typical manner. Similarly, neither IL‐17RA nor Rorγt expression by hematopoietic cells was required for disease development in this model. Conclusion: Despite prior reports suggesting that Th17 cells and IL‐17A are crucially involved in the pathogenesis of arthritis in K/BxN mice, the results presented here provide genetic evidence that IL‐17A and IL‐17F, IL‐17RA, and Rorγt expression by hematopoietic cells are dispensable for normal arthritis progression in the K/B/g7 mouse model system. We discuss potential explanations for the discrepancies between these 2 highly similar model systems. These findings plus those in other mouse models of arthritis provide insight regarding why therapeutic biologic agents targeting the Th17/IL‐17 axis are beneficial in some human rheumatic diseases but not others.